Anaplasma phagocytophilum—a widespread multi-host pathogen with highly adaptive strategies - Stuen, Snorre; Granquist, Erik G.; Silaghi, Cornelia (Frontiers in Cellular and Infection Microbiology, 2013)
The bacterium Anaplasma phagocytophilum has for decades been known to cause the disease tick-borne fever (TBF) in domestic ruminants in Ixodes ricinus-infested areas in northern Europe. In recent years, the bacterium has been found associated with Ixodes-tick species more or less worldwide on the northern hemisphere. A. phagocytophilum has a broad host range and may cause severe disease in several mammalian species, including humans. However, the clinical symptoms vary from subclinical to fatal conditions, and considerable underreporting of clinical incidents is suspected in both human and veterinary medicine. Several variants of A. phagocytophilum have been genetically characterized. Identification and stratification into phylogenetic subfamilies has been based on cell culturing, experimental infections, PCR, and sequencing techniques. However, few genome sequences have been completed so far, thus observations on biological, ecological, and pathological differences between genotypes of the bacterium, have yet to be elucidated by molecular and experimental infection studies. The natural transmission cycles of various A. phagocytophilum variants, the involvement of their respective hosts and vectors involved, in particular the zoonotic potential, have to be unraveled. A. phagocytophilum is able to persist between seasons of tick activity in several mammalian species and movement of hosts and infected ticks on migrating animals or birds may spread the bacterium. In the present review, we focus on the ecology and epidemiology of A. phagocytophilum, especially the role of wildlife in contribution to the spread and sustainability of the infection in domestic livestock and humans.